Pengaruh Media Sosial Terhadap Manajemen Pendidikan Islam: Antara Tantangan dan Peluang - Yogi Listiana (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The rapid development of social media has significantly impacted the management of Islamic education, presenting both opportunities and challenges. This study aims to analyze the influence of social media on Islamic education management by employing a Systematic Literature Review (SLR) approach. The research method involves identifying, evaluating, and synthesizing relevant literature from the past ten years to understand trends, benefits, and obstacles in utilizing social media for educational purposes. A total of 50 studies were reviewed, focusing on various aspects such as communication effectiveness, student interaction, and access to learning resources. The findings indicate that social media facilitates communication efficiency, enhances student engagement, and broadens access to Islamic educational resources. It has become an essential tool in delivering content, connecting students and educators, and fostering collaborative learning. However, challenges such as misinformation, lack of regulatory policies, and student distractions require strategic solutions. The study suggests implementing internal policies, providing teacher training, and utilizing social media analytics to optimize its use. In addition, integrating social media strategies with traditional Islamic teaching methods can enhance educational outcomes. These findings contribute to a deeper understanding of the role of social media in Islamic education management and offer recommendations for its effective implementation. Furthermore, the study highlights the need for further research to explore the long-term impacts of social media on Islamic education.